2007
DOI: 10.1111/j.1365-2133.2006.07725.x
|View full text |Cite
|
Sign up to set email alerts
|

Palmoplantar pustulosis and gluten sensitivity: a study of serum antibodies against gliadin and tissue transglutaminase, the duodenal mucosa and effects of gluten-free diet

Abstract: Patients with PPP should be screened for antibodies against gliadin and tTG. Those with antibodies can be much improved on a GFD regardless of the degree of mucosal abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 17 publications
(27 reference statements)
6
55
1
1
Order By: Relevance
“…The benefit of GFD has been shown to extend to patients who are antigliadin antibody-positive but without clinical and histological markers of celiac disease [1315]. These findings explain both a common trigger among respondents in this study being gluten and a patient-reported improvement of their psoriasis following a GFD.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The benefit of GFD has been shown to extend to patients who are antigliadin antibody-positive but without clinical and histological markers of celiac disease [1315]. These findings explain both a common trigger among respondents in this study being gluten and a patient-reported improvement of their psoriasis following a GFD.…”
Section: Discussionmentioning
confidence: 64%
“…Although the popular literature contains many dietary recommendations for psoriasis, the scientific literature is limited, especially among randomized controlled trials (RCT). The strongest scientific evidence exists for weight loss, particularly among obese psoriatic patients [310], and for gluten-free diets (GFD), which have been reported to improve psoriasis in a subset of patients with celiac-specific antibodies [1115]. Moreover, there is an absence of studies describing the effects of popular dietary recommendations and regimens, such as a Paleolithic diet or a vegetarian diet.…”
Section: Introductionmentioning
confidence: 99%
“…37 Although the lesions may occur in the setting of psoriasis elsewhere, it commonly affects patients lacking lesions elsewhere on the body. Also, there is evidence for an association between PPP and variations of the genes in the interleukin-19 subfamily of cytokines 38 and with gluten sensitivity, 39 the latter of which may on occasion also be associated with psoriasis vulgaris.…”
Section: Palmoplantar Psoriasis Phenotypementioning
confidence: 98%
“…The relationships between PPP and certain clinical features, such as gluten sensitivity, thyroid disease, diabetes mellitus and focal infections (like tonsillitis) have been demonstrated in recent studies [5, 6, 12, 13]. The increased frequency of thyroid disorders varies based on different studies, while the prevalence of thyroid pathologies is about 5% in the general population [3].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may contribute to this disease, including genetics, tobacco use and autoimmune disorders [3, 4]. Additional studies are necessary to clarify the relationship between PPP and autoimmune disorders, such as thyroid disease, gluten sensitivity and type 2 diabetes mellitus [3, 5, 6]. …”
Section: Introductionmentioning
confidence: 99%